Impact of Small-Sided Game Formats on Electromyographic Responses in College Students. - JuanFeng; Fernández, Alejandro Rodríguez; Trybulski, Robert; Grzywacz, Tomasz; Sawicki, Piotr; Clemente, Filipe Manuel (Journal of Sports Science & Medicine, 2025)
This study examined the effects of three small-sided game (SSGs) formats -1v1, 3 3v3, and 6v6- on muscle activation and fatigue during balance and jump performance tasks in collegiate athletes. Sixty healthy university students were randomly assigned to three groups (n = 20 each) for a 5-day SSG training program on standardized artificial turf. Training duration and recovery intervals were controlled, with player number and pitch size as independent variables. Muscle activity was measured using surface electromyography (sEMG) from the rectus femoris (RF) and biceps femoris (BF) during both the double-leg stance (DLS) balance task and the countermovement vertical jump (CMJ) task. Muscle activation and neuromuscular fatigue were quantified using the root mean square (RMS) and median frequency (MF) of the sEMG signal. Across all formats, CMJ elicited greater activation and fatigue than DLS (p < 0.001). The 6v6 format produced the highest activation (CMJ-RMS: 0.055 ± 0.012) and greatest fatigue (CMJ-MF: 62.5 ± 5.3 Hz), significantly exceeding 1v1 (p < 0.01). The 3v3 format showed peak DLS-MF (78.2 ± 6.7 Hz), higher than 1v1 (p=0.003), indicating optimal activation--fatigue balance. Temporally, 1v1 maintained higher DLS-MF on Days 1 - 3 (p < 0.05), reflecting short-term neuromuscular efficiency. RF activation was highest in 6v6 (p < 0.01), while BF fatigue resistance was greatest in 3v3 (p < 0.05). In conclusion, 6v6 maximizes activation and fatigue, 3v3 provides balanced activation-- fatigue, and 1v1 yields early neural efficiency but greater longterm fatigue. Future research should investigate longitudinal adaptations, sport-specific applications, and the influence of SSG formats on injury risk.